From theory to praxis: a reading project with university students - Portalatín Rivera, Nannette (2018)
The experience of a reading project addressed to seventh grade students of a school of the Department of Education of Puerto Rico during the years 2013-2015 is presented. University students, teachers in formation of the secondary Spanish Program of the University of Puerto Rico, offered Spanish classes through an active and contextualized methodology and used different strategies in order to improve school climate and academic achievement. In addition, they carried out projects of the International Education and Resource Network (IEARN), which allowed to strengthen the communication skills of adolescents and establish a learning community with several countries.